KEHIDUPAN SOSIAL EKONOMI MASYARAKAT SEKUPANG YANG BERPROFESI SEBAGAI SUPIR TAKSI TAHUN 2010 s/d 2016 - Putri Eka Sari; Arnesih Arnesih (CAHAYA PENDIDIKAN, 2018)
This research is a descriptive qualitative research with social and economic science approach. The method used there are several stages including (1) data collection techniques consist of observation, interview and documentation (2) data analysis consisting of data reduction, data presentation and conclusion (3) data validity by using data triangulation technique. This research indicates that the factors driving people to choose the profession as a taxi driver because in the former this profession has a high income, according to the infoman in the 90's only job there is taxi driver taxi jobs, and his working time in this profession is flexible and has no contract work. Taxi drivers in Sekupang Sub-district average their education is graduated from junior high school to high school. Religion owned by taxi drivers in Sekupang Sub-district is more dominant in Islam, but it is not possible that there is no religion. The number of children owned by each taxi driver in Sekupang District consists of two people up to three children in one family. The marital status of each taxi driver in Sekupang Sub-district is already family. Old Tiban people who work as a taxi driver in the district Sekupang not have health insurance, they use personal money if they need medical treatment. Taxi drivers in Sekupang Sub-district come from a variety of regions, but more dominates many who come from the West Sumatra region. Revenue that can be obtained decreased slightly compared to income in the early 90's, which in a day only get Rp. 50,000 to Rp. 100,000.Keywords: Socio-Economic Life, Taxi Driver, Sekupang Sub-district